Aeroelastic Phenomena and Pedestrian-Structure Dynamic Interaction on Non-Conventional Bridges and Footbridges - Borri, Claudio; Mannini, Claudio (Strumenti per la didattica e la ricerca, 2010)
Fluid-structure and pedestrian-structure interaction phenomena are extremely important for non-conventional bridges. The results presented in this volume concern: simplified formulas for flutter assessment; innovative structural solutions to increase the aeroelastic stability of long-span bridges; numerical simulations of the flow around a benchmark rectangular cylinder; examples of designs of large structures assisted by wind-tunnel tests; analytical, computational and experimental investigation of the synchronisation mechanisms between pedestrians and footbridge structures. The present book is addressed to a wide audience including professionals, doctoral students and researchers, aiming to increase their know-how in the field of wind engineering, bluff-body aerodynamics and bridge dynamics.